Instructors’ expressive nonverbal behavior hinders learning when learners’ prior knowledge is low - Wang, Mengke; Chen, Zengzhao; Shi, Yawen; Wang, Zhuo; Xiang, Chengguan (Frontiers in Psychology, 2022)
This study investigated the influence of instructors’ expressive nonverbal behavior and nonexpressive nonverbal behavior in video lectures on students’ learning performance and affective experience. We conducted two rounds of experiments using the same materials and procedures, the only difference being the participants. In each round of experiments, participants were randomly assigned to expressive condition or nonexpressive condition. 227 rural primary school sixth-graders took part in experiment 1, participants in expressive condition had better affective experiences and perceived tasks as less difficult, but had lower learning performance than participants in nonexpressive condition. 175 sixth-graders from urban primary schools participated in experiment 2. The results showed that instructors’ expressive nonverbal behavior also improved students' affective experience and reduced students' perception of task difficulty, but there was no significant difference in learning performance between two groups. Comparing the pretest scores of students in the two experiments, it was found that the pretest scores of participants in experiment 2 were higher than those in experiment 1. Overall, instructors' expressive nonverbal behavior can improve students' affective experience and reduce their perception of task difficulty. However, when students' prior knowledge is relatively low, instructors' expressive nonverbal behavior hinders students' learning performance. We suggest that teachers adopt expressive nonverbal behavior when lecturing because it is beneficial to maintain students' long term interest in learning. However, it should be noted that the difficulty of learning material should be determined by students' prior knowledge.